Potential of aquatic fungi derived from diverse freshwater environments to decolourise synthetic azo and anthraquinone dyes - Junghanns, C.; Krauss, G.; Schlosser, D.
A total of 37 strains of aquatic hyphomycetes and 95 fungal isolates derived from diverse freshwater environments were screened on agar plates for the decolourisation of the disazo dye Reactive Black 5 and the anthraquinone dye Reactive Blue 19. The decolourisation of 9 azo and 3 anthraquinone dyes by 9 selected aquatic fungi was subsequently assessed in a liquid test system. The fungi were representatives of mitosporic anamorphs, and 6 strains had proven ascomycete affiliations. For comparison, 5 white rot basidiomycetes were included. The majority of dyes were decolourised by several mitosporic aquatic isolates at rates essentially comparable to those observed with the most efficient white rot fungus. Under certain conditions, particular aquatic strains decolourised dyes even more efficiently than the best performing white rot basidiomycete. Upon fungal treatment of several dyes, new absorbance peaks appeared, indicating biotransformation metabolites. All together, these results point to the potential of fungi occurring in freshwater environments for the treatment of dye-containing effluents.
Keywords: ANTHRAQUINONE DYES; AQUATIC HYPHOMYCETES; ASCOMYCETES; AZO DYES; MITOSPORIC FUNGI; TEXTILE DYES